Handbook of Medical Imaging Physics and Psychophysics. - Van Metter, Richard; Beutel,Jacob; Kundel,Harold (SPIE, 2000)
Annotation This book examines x-ray imaging physics and reviews linear systems theory and its application to signal and noise propagation. The first half addresses the physics of important imaging modalities now in use: ultrasound, CT, MRI, and the recently emerging flat panel x-ray detectors and their application to mammography. The second half describes the relationship between image quality metrics and visual perception of the diagnostic information carried by medical images.Softcover version of PM79.
Keywords: Diagnostic imaging -- Handbooks, manuals, etc.; Imaging systems in medicine -- Handbooks, manuals, etc.; elektronické knihy; electronic books